2018
DOI: 10.1111/fire.12144
|View full text |Cite
|
Sign up to set email alerts
|

CEO Incentives and Corporate Innovation

Abstract: Using scaled wealth‐performance sensitivity as my measure of Chief Executive Officer (CEO) incentives, and utilizing cross‐sectional variations in industry innovativeness, product market competition and firms’ degree of exposure to the market for corporate control for identification purposes, I find that higher long‐term incentives that stem from CEO holdings of unvested options are associated with greater subsequent corporate innovation in innovative industries, competitive product markets, and firms more exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 55 publications
(82 reference statements)
2
39
0
1
Order By: Relevance
“…Hence, the results of the current study also complement other studies that find a positive impact of greater CEO incentives (that promote long-term performance) on overall firm performance. Such studies have observed incentive schemes to not only impact firm productivity, firm value and profitability (Jensen and Murphy, 1990;Sun et al, 2009;Nguyen, 2018) but also corporate social performance (Deckop et al, 2006). The results also complement more recent studies that observe CEO risk-taking incentives to encourage risky investments (Chen, 2017), as well as enhance innovation output quantity and quality (Mao and Zhang, 2018),…”
Section: Ceo Dominance and Firm Innovationsupporting
confidence: 78%
“…Hence, the results of the current study also complement other studies that find a positive impact of greater CEO incentives (that promote long-term performance) on overall firm performance. Such studies have observed incentive schemes to not only impact firm productivity, firm value and profitability (Jensen and Murphy, 1990;Sun et al, 2009;Nguyen, 2018) but also corporate social performance (Deckop et al, 2006). The results also complement more recent studies that observe CEO risk-taking incentives to encourage risky investments (Chen, 2017), as well as enhance innovation output quantity and quality (Mao and Zhang, 2018),…”
Section: Ceo Dominance and Firm Innovationsupporting
confidence: 78%
“…Radical innovation is a crucial driver of enhanced organizational performance leading to competitive advantage (Ancona and Caldwell, 1987;Nguyen, 2018). An organization's radical innovation-oriented activities often require high-technology techniques and human resources to achieve these goals (Barba-Arag on and Jiménez-Jiménez, 2020).…”
Section: Theoretical Framework 21 Radical Innovationmentioning
confidence: 99%
“…Isada and Isada (2017) demonstrated that innovation could be divided into two basic types according to its novelty, namely, radical innovation and incremental innovation. Radical innovation involves significant improvements in products and services and the provision of new products and services (Nguyen, 2018). Incremental innovation involves slight changes in technology and some new value or differentiation in current products, services and technology (Okuyama, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, an increase in the size of the tournament prize (i.e., the external pay gap) is expected to increase the aspirant's efforts and expected performance (Coles et al, 2020). Coles et al (2018) document empirical evidence of Tobin's Q being positively associated 1 For example, Hirshleifer et al (2012) demonstrate that overconfident CEOs are better innovators; Faleye et al (2014) show that better-connected CEOs innovate more; Sunder et al (2017) find that CEOs' sensation-seeking trait is associated with better innovation outcomes; and Nguyen (2018) examines the impact of CEO incentives on corporate innovation.…”
Section: Introductionmentioning
confidence: 99%